Penerapan Metode Inkuiri untuk Meningkatkan Aktivitas dan Motivasi Belajar Kelompok melalui Lesson Study - Lalu Muhammad Fauzi (Universitas Syiah Kuala, 2015)
Abstract. The main objective of this research was to determine the extent of the effective implementation of lesson study with inquiry learning methods application, that purposed to improve learning motivation and activity groups in the preparation of instruments and quality analysis instruments. The research conducted a study in Evaluasi Hasil Belajar Matematika subject at mathematics education department of STKIP Hamzanwadi Selong. This study used a model of action research through lesson study. The subject of this study was the fifth semester of preservice students consisting of 28 students. Data collected used observation and field notes. Data processing techniques used qualitative descriptive technique. Lesson study research results as a model of collaborative coaching educator and collegative can be used as a model for teaching faculty guidance to students. Implementation of lesson study consisted of four cycles and three stages namely plan, do and see. At each cycle of increased activity and student motivation to learn both individually and in groups. Students gain knowledge and experience of the planning and implementation of innovative learning.Keywords: Lesson study, methods of inquiry learning, learning motivation, activities group